PENGARUH SNOWBALL THROWING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD GUGUS V KOTA BENGKULU - Tria Febrina; Neza Agusdianita (Universitas Bengkulu, 2023)
This research’s aim to know the application model influence of snowball throwing to the result of learning mathematic at geometry material to 5th grade student group V Bengkulu City. This kind of research is quantitative research. The methods is Quasy Eksperimental with the design in the matching only pretest posttest contol group design. The population of the research is entire 5th Grade griup V elementary school Bengkulu City. The sampel in this research are divided in two group, that is 5th A grade student in elementary school 2 Bengkulu City as a eksperiment group, and 5th B 9 grade student in elementary school 9 Bengkulu City as a control group. The instrument is the result of learning of learning tes with multiple choicd that gift by pretest before the study is begin and posttestafter the study is over. The data will be analyzed with descripve and analysis, that T-test, the result is with the value of Tcountis 3,42 and the value of Ttabelis 1,997. So with Tcount>Ttable at significant 5%, so we can conclude that there is the application models influence of snowball throwing to the result of learning mathematic at geometry material to 5th grade student group V Bengkulu City.